Attention Deficit Hyperactivity Disorder Among Sample of Elementary schoolchildren in The Southern District in Babylon province - Abdulmahdi A.Hasan (Genius Journals, 2022)
ADHD (attention deficit hyperactivity disorder) is one of the most common chronic childhood illnesses and the most common neurobehavioral disorder in children, characterized by inattention and impulsivity. This study aims to measure the prevalence of Attention Deficit Hyperactivity Disorder in a sample of primary school children in the southern district of Al- Hilla city and identifying some of its correlates. Result shows that the most of the sample are increase in the rate in men more than women, ADHD include (11%) male while (3%) female and shows that ( 10% ) of the sample have smoking positive with ADHD while(4%) have smoking negative with ADHD, also the result shows that most of the sample study (8%) low school performance with ADHD ,while ( 6% ) HAVE normal with ADHD. The study recommend for further comprehensive scientific studies are needed to assess the extent of this problem in Iraq and establishing child psychiatrist unit in Babylon province to manage ADHD cases and giving drugs freely.
Keywords: ADHD; Elementary; schoolchildren; Babylon province